Sustainable Natural Printing of Cotton Fabric Without Metal-Based Mordant - Bivuti Vusan Mondal; S M Fijul Kabir; Ayub Ali; Md. Abdul Hannan (Journal of Natural Fibers, 2022)
Endeavors on scoured and bleached cotton knit fabric to print with natural dyes and natural thickeners were made avoiding the use of detrimental metal-based mordanting agents. Three different natural dye sources (Rose flower-Rosa indica, Teak leaf-Tectona grandis and Tamarind-Tamarindus indica seed husk) extracted in aqueous medium were applied on 100% cotton knit fabric with three different thickeners prepared from the powder of Guar gum-Cyamopsis tetragonoloba, mango seed-Mangifera indica and tamarind seed-Tamarindus indicaon. The printed samples exhibited excellent wash fastness with grading 4–5 for all printed samples, light fastness 7 for tamarind seed husk and tamarind seed, rose flower and tamarind seed printed fabrics and rubbing fastness 4–5 for all printed fabrics. Dye-fiber bond formation was confirmed by FTIR, which revealed phenomena of strong covalent bond between dye and fiber molecules. Environmental impact assessments, chemical oxygen demand (COD) of 0–158 mg/L and total suspended solid (TSS) of 1–55 mg/L indicated that the wastewater generated was safe to discharge to the environment without treatment. Other essential features, determination of K/S value, CIE lab data and durability of printing paste demonstrated successful application of natural dyes and thickeners for printing cotton fabric.